2010
DOI: 10.1177/1948550610368315
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Liking From Bivariate Attitude Similarity

Abstract: There exists robust evidence for attitude similarity as a major cause of interpersonal liking, but previous research has ignored the case of similarity in attitudinal ambivalence or indifference. Whereas extensions of Heider's balance theory predict that people are indifferent toward other's ambivalence versus indifference, Byrne's reinforcement theory of attraction predicts that people prefer interaction partners that match their own degree of ambivalence and indifference. Furthermore, Shafir's principle of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
0
4
1
Order By: Relevance
“…An ambivalent person who agrees should be more liked than a person who is ambivalent but disagrees. Furthermore, contrary to Ullrich and Krueger's (2010) results, when another person offers agreement, an ambivalent person might actually prefer a person who is unconflicted rather than ambivalent, if the unconflicted person is viewed as more capable in reducing the social perceiver's own ambivalence. To date, the potential interplay of an individual's ambivalence and a target's strength of position in determining interpersonal attraction remains unexamined.…”
Section: Implications Beyond Selective Exposurecontrasting
confidence: 77%
See 1 more Smart Citation
“…An ambivalent person who agrees should be more liked than a person who is ambivalent but disagrees. Furthermore, contrary to Ullrich and Krueger's (2010) results, when another person offers agreement, an ambivalent person might actually prefer a person who is unconflicted rather than ambivalent, if the unconflicted person is viewed as more capable in reducing the social perceiver's own ambivalence. To date, the potential interplay of an individual's ambivalence and a target's strength of position in determining interpersonal attraction remains unexamined.…”
Section: Implications Beyond Selective Exposurecontrasting
confidence: 77%
“…For example, one open question is how an individual's ambivalence might affect liking for a target depending on the target's attitude and level of ambivalence. Research suggests that an ambivalent person prefers another person who is ambivalent rather than indifferent (Ullrich & Krueger, 2010), but the current findings suggest that the effects may change when one varies the other person's stance on the issue (because ambivalence and indifference each represented neutral attitudes in the Ullrich & Krueger, 2010, research). An ambivalent person who agrees should be more liked than a person who is ambivalent but disagrees.…”
Section: Implications Beyond Selective Exposurementioning
confidence: 51%
“…The purpose of this study was to test the moderation of attitudinal ambivalence in the TPB on adolescent marijuana use, replicating and extending the findings of Conner et al (2003), using an ambivalence indicator that was not susceptible to the methodological weaknesses identified by Ullrich and Krueger (2010) in their earlier critique of potential ambivalence measures. The secondary data analysis performed on the NSPY involved two separate hierarchical multiple regression models: the first explored the moderating effects of ambivalence on intentions to use marijuana; the second tested the moderation on actual marijuana use 1 year later.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, people were asked to report their preference between two targets who expressed either ambivalence (i.e., expressing oneself in part very positively and in part very negatively) or indifference (i.e., expressing oneself neutrally) about several ambivalent attitude objects (e.g., euthanasia). Researchers found that ambivalent participants tended to prefer the ambivalent target relative to the indifferent target ( Ullrich and Krueger, 2010 ). Altogether, these findings suggest that similar levels of OA (i.e., shared attitudinal structure) might cue interpersonal liking.…”
Section: Introductionmentioning
confidence: 99%